15 - EVALUATION OF THE FUNCTIONALITY DEGREE IN VICTIMS OF ENCEPHALIC VASCULAR ACCIDENT (EVA) THROUGH THE BARTHEL INDEX AFTER HYDROTHERAPY INTERVENTION WITH THE BAD RAGAZ METHOD . (Fiep Bulletin - online, 2011)
Encephalic Vascular Accident (EVA) is one of the main causes of neurological consequences. The patient may present abnormal positions and movements, structural deformities and limitation in the activities of daily life (ADLs). Through the application of the Barthel Index (BI) and intervention of the Bad Ragaz Ring Method (BRRM) the research aimed to verify the responses related to the biomechanical alignment of the trunk and the degree of functionality of a patient with EVA stroke after the aquatic therapy intervention. This research is characterized by a case study of cause-effect, with exploratory character. It was selected a female patient, 55 years-old, with EVA stoke diagnosis at 17 months ago. As an evaluation and re-evaluation procedure was used the simetrograph and the BI questionnaire. Fourteen appointments of 45 minutes each had been made, in the period of two Months. The results obtained in IB pre and post test were identical reaching a simple percentage score of 90 points. Although the Barthel Index is widely used because of the trustworthiness and practicality of implementation there is little degree of each topic, leaving to consider, so that refined as the state of patient dependency. But the BRRM made possible to the patient improvement of the postural symmetry.
Keywords: Activities of Daily Life (ADLs); Barthel Index (BI); Encephalic Vascular Accident (EVA); Hydrotherapy and Bad Ragaz Ring Method (BRRM)